Handedness and White Matter Networks. (February 2021) - Budisavljevic, Sanja; Castiello, Umberto; Begliomini, Chiara
The development and persistence of laterality is a key feature of human motor behavior, with the asymmetry of hand use being the most prominent. The idea that asymmetrical functions of the hands reflect asymmetries in terms of structural and functional brain organization has been tested many times. However, despite advances in laterality research and increased understanding of this population-level bias, the neural basis of handedness remains elusive. Recent developments in diffusion magnetic resonance imaging enabled the exploration of lateralized motor behavior also in terms of white matter and connectional neuroanatomy. Despite incomplete and partly inconsistent evidence, structural connectivity of both intrahemispheric and interhemispheric white matter seems to differ between left and right-handers. Handedness was related to asymmetry of intrahemispheric pathways important for visuomotor and visuospatial processing (superior longitudinal fasciculus), but not to projection tracts supporting motor execution (corticospinal tract). Moreover, the interindividual variability of the main commissural pathway corpus callosum seems to be associated with handedness. The review highlights the importance of exploring new avenues for the study of handedness and presents the latest state of knowledge that can be used to guide future neuroscientific and genetic research.